The Relationships between Muscle Fiber Characteristics, Intramuscular Fat Content, and Fatty Acid Compositions in M. longissimus lumborum of Hanwoo Steers - Joo, Seon-Tea (Korean J Food Sci Anim Resour, 2017)
The objective of this study was to investigate the relationship between muscle fiber characteristics, intramuscular fat (IMF) content, and fatty acids composition in longissimus lumborum (LL) muscle from Hanwoo steers. The LL muscles were obtained from four quality grades (QG) carcasses and subjected to histochemical analysis. There were significant (p<0.05) differences in fiber number percentage (FNP) and fiber area percentage (FAP) of muscle fiber types among muscles from four QGs. Both FNP and FAP of type I increased while those of type IIB decreased with increasing QG from QG 2 to QG 1(++) (p<0.05). Also, with increasing QG, the saturated fatty acid (SFA) proportion decreased while monounsaturated fatty acid (MUFA) increased significantly (p<0.05). IMF content was positively correlated with both FNP and FAP of type I, but negatively correlated with those of type IIB. The proportions of SFA and MUFA were significantly (p<0.001) correlated with both type I and IIB composition. These results implied that muscle fiber type composition is an important factor influencing fatty acid composition in LL muscle of Hanwoo steer.